Analisis Asas Kebebasan Berkontrak Terhadap Perjanjian Pinjaman Bridging Financing - Lina Shabrina (Faculty of Law, Diponegoro University, 2021)
AbstrakUtang piutang merupakan salah satu bentuk perjanjian yang diatur di dalam Buku III KUH Perdata, yang selain tunduk pada Pasal 1320 tentang Syarat Sah perjanjian, juga tunduk pada Asas-asas perjanjian antara lain Asas Kebebasan Berkontrak, Asas Konsensual, Asas Itikad Baik dan Kepatutan, dan Asas Pacta Sun Servanda. Metode penulisan bersifat normative, deskriptif dengan tujuan untuk mengkaji akibat hukum jika terjadi wanprestasi. Kesimpulan dalam paparan ini adalah debutur yang melakukan wanprestasi dikenakan kewajiban membayar ganti kerugian, adapun penyelesaianya dengan cara non litigasi. Kata Kunci : utang piutang, syarat sah perjanjian, wanprestasiAbstractReceivables are a form of agreement regulated in Book III of the Civil Code, which in addition to being subject to Article 1320 concerning the Legal Terms of the agreement, are also subject to agreement principles including the principle of freedom of contract, consensual principle, principle of good faith and propriety, and principle of pact. Sun Servanda. The writing method is normative, descriptive with the aim of studying the legal consequences if there is a default. The conclusion in this presentation is that debtors who default are subject to the obligation to pay compensation, as for the settlement by non-litigation. Keyword : accounts payable, legal terms of agreement, default